Maternal use of drugs and preeclampsia. Issue 12 (15th December 2019) - Sahlman, Heidi; Koponen, Marjaana; El‐Nezami, Hani; Vähäkangas, Kirsi; Keski‐Nisula, Leea
Abstract : Aims: The aim was to compare and describe maternal use of drugs between women with preeclampsia and controls and to estimate the possible association with preeclampsia. Methods: The study cohort was collected from the Kuopio University Hospital Birth Register, which includes information about all women who gave birth in Kuopio University Hospital during the years 2002–2016, including information from approximately 36 000 parturients, of whom 1252 had preeclampsia. Maternal use of 16 groups of drugs during pregnancy was analysed from all women with preeclampsia and 1256 controls. Results: Every second woman had used at least 1 drug during pregnancy but those with preeclampsia had used significantly more than the controls (cases 59.5% vs controls 35.5%; p < 0.001). In both study groups, the most commonly used drugs were antibiotics (cases 19.5%, controls 17.0%), antihypertensives (cases 29.0%, controls 7.6%) and paracetamol (cases 13.1%, controls 5.9%). Women with preeclampsia had used significantly more benzodiazepines, paracetamol, antihypertensives and acid‐suppressive drugs than the women in the control group ( p < 0.05). Conclusions: Women with preeclampsia were more likely to use medicines during pregnancy. While the association between benzodiazepines, antihypertensives and acid‐suppressive drugs and preeclampsia may be explained by reverse causation, the association of paracetamol with preeclampsia remains to be clarified. Because paracetamol is a frequently used drug, more information about its safety during pregnancy including its role in preeclampsia is urgently needed.